Using Inerter-based Damper for Offshore Semi-submersible Platform Vibration Control - Ma, Ruisheng (Curtin University, 2020)
Semi-submersible platforms are widely utilized but may subject to excessive vibrations during their service lives. This thesis aims to study the performance of inerter-based control systems in reducing the vibrations of semi-submersible platforms subjected to wave load. Three inerter-based control systems are proposed, and extensive analytical and experimental studies are performed to evaluate the control effectiveness of these inerter-based control systems.